2020
DOI: 10.3390/app10020590
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of a Nanostructured Titanium Oxide Layer with Self-Assembled Monolayers for Biomedical Applications: Surface Properties and Biomechanical Behaviors

Abstract: This study investigated the surface properties and biomechanical behaviors of a nanostructured titanium oxide (TiO) layer with different self-assembled monolayers (SAMs) of phosphonate on the surface of microscope slides. The surface properties of SAMs were analyzed using scanning electron microscopy, X-ray photoemission spectroscopy, and contact angle goniometry. Biomechanical behaviors were evaluated using nanoindentation with a diamond Berkovich indenter. Analytical results indicated that the homogenous nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This can influence cellular behavior such as proliferation, adhesion, and migration, and thereby promote osseointegration and tissue healing following dental implant placement [24]. A study conducted by Lan et al [25] observed the water contact angles and the surface wettability characteristics of a TiO 2 -modified surface with four types of phosphonic acid compounds, along with the control. It was found that the TiO 2 surface treated with 11-phosphonoundecanoic acid (PUA) had the best hydrophilic surface, with an average contact angle measurement of 68.8 ± 0.7.…”
Section: Discussionmentioning
confidence: 99%
“…This can influence cellular behavior such as proliferation, adhesion, and migration, and thereby promote osseointegration and tissue healing following dental implant placement [24]. A study conducted by Lan et al [25] observed the water contact angles and the surface wettability characteristics of a TiO 2 -modified surface with four types of phosphonic acid compounds, along with the control. It was found that the TiO 2 surface treated with 11-phosphonoundecanoic acid (PUA) had the best hydrophilic surface, with an average contact angle measurement of 68.8 ± 0.7.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, biosensors are been increasingly applied in clinical analysis due to their portability and point of care testing, which can analyze real biological samples in routine clinical use [25] . The incorporation of nanotechnology in the design of biosensors has improved the detection of biological specimens, as the preparation of biointerfaces of self-assembled monolayers (SAMs), improving biocompatibility and resistance against nonspecific adsorption [26] , [27] , [28] , [29] .…”
Section: Biosensorsmentioning
confidence: 99%
“…There are various material approaches that can be used to add bioactivity to bulk materials. Broadly, these are changes in the chemistry (Trino et al, 2018), stiffness (Behaviors et al, 2020) and topography (Hasan et al, 2017;Damiati et al, 2018;Behaviors et al, 2020). Different scaffolds have been utilized to facilitate the delivery of RNA, such as polymers-based scaffolds, ceramic-based scaffolds, and metal-based scaffolds.…”
Section: Orthopedic Tissue Engineeringmentioning
confidence: 99%